Comparison of Real Response and Theoretical Modeling of Pavement with Thick Asphalt Layers under Heavy Traffic Load - Jingsong Shan; Hongmei Shao; Qiuzhong Li; Peili Sun (Advances in Civil Engineering)
Two kinds of asphalt pavement with thick asphalt layers were used to construct two samples. In structure I, a semirigid base and graded crushed stone subbase were used. In structure II, a granular base and semirigid subbase layer were used. Responses of the two structures under traffic loads were measured using optical fiber sensors, and the differences between theoretical model results and field measurements were analyzed. Field measurements show that vertical compressive stress in structure I is larger than that in structure II. The maximum tensile strain of the asphalt layer is located at the bottom of the AC-25C layer in structure I and at the bottom of the AC-25F layer in structure II. The latter is significantly larger than the former, indicating the possibility of fatigue cracking induced by traffic load is higher in structure II. The measured tensile horizontal strain at the bottom of the semirigid layer is relatively low (<30εμ) in both structure I and structure II. In theoretical model, static modulus, dynamic modulus, and interface bonding ability are considered and theoretical responses are calculated. There are significant differences between the theoretical results and field test data. In the theoretic model, the material properties of layers and bonding status of adjacent layers all influence the results. In order to reduce the difference between the calculated and measured results, numerous material tests and field tests should be carried out.